Identification and prioritization of effective approaches for public education and participation in household waste management (A case study: Tehran, Iran) - Esmatossadat Hashemi; Hooman Bahmanpour; Amir Hesam Hassani; Amir Hooman Hemmasi (Anthropogenic Pollution)
This study aimed to identify and prioritize effective methods to increase public education and participation in household waste management in Tehran (capital of Iran) as a pilot city. First, baseline data were gathered through a library research process, and then 33 waste management experts were employed as a panel to complete a researcher-made questionnaire on a Likert scale. Statistical tests and factor analysis were used to analyze the data and determine the relationships between the components. According to the results, among the determined 27 items of identifying and developing educational approaches for public participation in waste management, the item "environmental literacy" ranked first with an average score of 4.52, and the item "individual training" ranked lowest with an average score of 3.91. The final model includes five levels of factors influencing environmental education and promoting public participation. Normed Fit Index (NFI=0.96), Relative Fit Index (RFI=0.96), and Comparative Fit Index (CFI=0.98) indicated that the proposed model had a good fit. The Goodness of Fit Index (GFI=0.91) and the Adjusted Goodness of Fit Index (AGFI=0.89) also confirmed the goodness of fit of the model. Effective municipal waste management requires active participation of citizens, which can be achieved by providing environmental education.